Biotic causes of oak forests weakening in Zhytomyr Region - Andreieva, O. Yu.; Zhytova, O. P.; Martynchuk, I. V.; Vlasiuk, V. P.; Stehniak, V. D. (Forestry and Forest Melioration, 2019)
Introduction Oak stands occupy about 15 % of the forest area in Zhytomyr Region. Recently their health condition has worsened. To recognize the biotic causes of oak decline, it is necessary to provide their monitoring, prediction, and prevention. The aim of the research was to reveal the special aspects of harmful insects and pathogens spread in oak stands in Zhytomyr Region. Materials and Methods The Database of Ukrderzhlisproekt Production Association (by 2011), statistical reporting of the Zhytomyr Regional Forestry and Hunting Department and State Specialized Forest Protection Enterprise “Vinnytsyalisozahyst” was analyzed for the State Forest Enterprises in Zhytomyr Region as well as the results of own field studies in 2013–2019 in oak stands in the mentioned region. The specific foci area was evaluated by dividing the absolute foci area, expressed in hectares, by the area of deciduous stands, expressed in thousands of hectares. Results Since the beginning of the millennium, two outbreaks of foliage browsing insects have been registered in the region. Polyphagous geometrids Operophtera brumata (Linnaeus, 1758) and Erannis defoliaria (Clerck, 1759) dominated in the foci, and several other Lepidoptera from families Tortricidae, Noctuidae and Pyralidae were present. The first outbreak began in 2002 and covered over 16 thousand ha. It ceased in 2008. The second outbreak started in 2010. The threat of foliage damage in 2012–2014 exceeded 50 % at 16.6–18.7 % from the total foci area, and in other years, up to 2018, the threat of foliage damage was below 25 %. Maximal foci area (over 3,000 ha) was registered in the State Forest Enterprises Berdychivske, Zhytomyrske and Gorodnytske, and maximal specific foci area in the State Forest Enterprise Gorodnytske (633.5 ha per 1,000 ha of oak stands). Oak foliage was also damaged by Melolontha hippocastani Fabricius, 1801 and Melolontha melolontha (Linnaeus, 1758) (Scarabaeidae), oak flea beetle Altica quercetorum Foudras, 1860) (Chrysomelidae), Lymantria dispar (Linnaeus, 1758), Euproctis (Euproctis) chrysorrhoea (Linnaeus, 1758) and Calliteara pudibunda (Linnaeus, 1758) (Lymantriidae). The largest area of diseases in oak stands was registered for oak bacterial cancer (the pathogen Pseudomonas quercus Schem) and fungal diseases caused by Phellinus robustus Bourd. et Galz. and Armillaria sp. The area of oak bacterial cancer increased in the years when foliage browsing insects’ outbreaks were decaying – in 2008 and 2013. The largest area of pests and diseases were registered in the State Forest Enterprise Berdychivske. 6 Figs., 1 Table, 27 Refs.